Corporate governance and foreign ownership in the Islamic capital market of Kuwait - Boresli, Naser S; Haron, Razali; Hassan, Rusni (Asian Economic and Social Society, 2023)
This paper aims to explain the corporate governance factors of foreign ownership in the Islamic capital market in Kuwait. A triangulated lens of agency, stewardship, and resource dependence is used to collect data from 58 listed firms on Boursa Kuwait. The findings suggest that board size; risk management; Chief Executive Officer (CEO) duality; environmental, social, and governance (ESG) practices; and debt to equity are significant determinants of attracting foreign capital. Board independence, firm size, and return on assets are significant factors, though there are narratives to the contrary in the literature. These results are important as the Kuwaiti market has demonstrated evidence for unifying the three theoretical perspectives of resource dependence (board size, risk management), agency (CEO duality), and stewardship (ESG practices and capital structure). This unification will contribute to further development of the corporate governance theory and policy in the future in terms of inclusion and exclusion of corporate governance frameworks.